Internalization of Social Care Character Values on the Moral Behavior of Students at SD Negeri 2 Ganti, Central Lombok Regency - Sahlum; Badarudin; Edy Waluyo (Lembaga Bale Literasi, 2026)
This study aims to describe the process of internalizing social care character values, identify its supporting and inhibiting factors, and analyze its influence on students' moral behavior at SD Negeri 2 Ganti, Central Lombok Regency. A qualitative descriptive design was employed. Informants were selected through purposive sampling and comprised the principal, class teachers, religious education teachers, education personnel, and selected students. Data were collected through participant observation, semi-structured interviews, and documentation, then analyzed using the Miles, Huberman, and Saldaña interactive model of data condensation, data display, and conclusion drawing and verification. Trustworthiness was maintained through source and technique triangulation, prolonged engagement, persistent observation, and member checking. The findings show that social care values are internalized through teacher role modeling, habituation, integration into classroom learning, religious activities, communal work (gotong royong), routine almsgiving, orphan care programs, and consistent school culture. Supporting factors include the principal's instructional leadership, teacher commitment, a conducive school culture, parental support, and continuity of character programs. Inhibiting factors include excessive exposure to digital media, weak parental supervision, uneven student awareness, and limited time allocation for character education. The internalization process contributes positively to students' empathy, responsibility, cooperation, discipline, politeness, tolerance, and prosocial moral behavior. The study concludes that sustained collaboration among school, family, and community is essential to strengthen character education and recommends that elementary schools institutionalize experience-based character programs as an integral part of school culture.